Self‐Assembled Aptamer Nanoconstruct: A Highly Effective Molecule‐Capturing Platform Having Therapeutic Applications. Issue 3 (19th October 2018) - Lee, Jihyun; Lee, Junseok; Ree, Brian J.; Lee, Yeong Mi; Park, Hyeongmok; Lee, Tae Geol; Kim, Jeong Hun; Kim, Won Jong
Abstract: Although the aptamer is a promising tool for binding and controlling the activity of a specific target molecule, its relatively low stability and capturing efficiency are major obstacles for its direct use in therapeutic applications. Herein, a 3D molecular capture system named the "constructed aptamer (CA)" is reported, which is formulated by the self‐assembly of the human vascular endothelial growth factor (hVEGF) aptamer block and Y‐shaped DNA blocks. The serum stability and target capturing efficiency exhibited by the CA are greater than that observed with the oligomeric aptamer and randomly amplified aptamer. In addition, successful intracellular uptake is observed by confocal laser scanning microscopy using fluorescence labeled CA. Finally, an enhanced antitumor effect is demonstrated in vivo, owing to the efficient inhibition of angiogenesis. Overall, the designed CA has great potential as a therapeutic platform for capturing a specific disease‐related molecule such as VEGF. Abstract : A self‐assembled aptamer nanoconstruct is easily prepared by self‐assembly of functional DNA blocks and structural DNA blocks, size‐controlled by blunt end formation. Owing to an enhanced stability and an excellent capturing efficiency, vascular endothelial growth factor (VEGF) capturing constructed aptamers can be exploited as a promising anti‐VEGF therapy including anti‐angiogenesis or antitumor therapy.